Pistacia vera Extract Potentiates the Effect of Melatonin on Human Melatonin MT1 and MT2 Receptors with Functional Selectivity - Nedjma Labani; Florence Gbahou; Marc Noblet; Bernard Masri; Olivier Broussaud; Jianfeng Liu; Ralf Jockers (MDPI AG, 2023)
Melatonin is a tryptophan derivative synthesized in plants and animals. In humans, melatonin acts on melatonin MT1 and MT2 receptors belonging to the G protein-coupled receptor (GPCR) family. Synthetic melatonin receptor agonists are prescribed for insomnia and depressive and circadian-related disorders. Here, we tested 25 commercial plant extracts, reported to have beneficial properties in sleep disorders and anxiety, using cellular assays (2─[125I]iodomelatonin binding, cAMP inhibition, ERK1/2 activation and β-arrestin2 recruitment) in mock-transfected and HEK293 cells expressing MT1 or MT2. Various melatonin receptor-dependent and -independent effects were observed. Extract 18 (Ex18) from Pistacia vera dried fruits stood out with very potent effects in melatonin receptor expressing cells. The high content of endogenous melatonin in Ex18 (5.28 ± 0.46 mg/g extract) is consistent with this observation. Ex18 contains an additional active principle that potentiates the effect of melatonin on Gi protein-dependent pathways but not on β-arrestin2 recruitment. Further active principles potentiating exogenous melatonin were detected in several extracts. In conclusion, we identified plant extracts with various effects in GPCR-based binding and signalling assays and identified high melatonin levels and a melatonin-potentiating activity in Pistacia vera dried fruit extracts that might be of therapeutic potential.